Northern Shrimp (Pandalus borealis) on Flemish Cap Surveys 2003 and 2004 - Casas-Sánchez, José Miguel; Río-Iglesias, José Luis del; González-Troncoso, Diana (2004)
Since 1988, a stratified random summer bottom trawl survey in Flemish Cap (NAFO Regulatory Area of Div. 3M) was conducted by UE. Since 2003 the trawl vessel was replaced, the new vessel was calibrated and the indexes transformed. The lack of time has no permitted to transform the biomass and abundance shrimp indexes of the whole time series. So, the indexes in the series from 1988 to 2002 have not been changed by now and only the 2003 and 2004 indexes from the R/V Vizconde de Eza have been transformed to the R/V Cornide de Saavedra scale, to make them comparable to the results obtained in previous years. The shrimp catches taken with the same gear type Lofoten by both vessels from comparative fishing trials were very different, not only in weight but also in number. These results were interpreted on main differences between both vessels: trawl winch with an automatic control of the warp tension, higher vertical opening in the net and trawl warp length longer in the new vessel. Also, in the catches of the new vessel the presence of young shrimps was higher than in the old one. Because of this, abundance and biomass indexes from 2003 and 2004 were transformed using two methods based in conversion of CPUE and length frequencies and comparing the resulting estimates between them. Although there was not severe differences between these two methods, the marked differences in the length distribution of the catches makes the catch rate strongly dependent of the fish length (Warren, 1997), and thus we think the length conversion method reflects better the differences between the vessels. About the situation of the stock, a significan decreasing shrimp abundance and biomass is observed in the last two years (2003-2004), probably due to declining of 3 and 5 age-classes. Also, the strong presence of the youngest model groups (age 1 and 2) in the catches predicts good recruitment in next years.